Emergence of Plasmids Co-Harboring Carbapenem Resistance Genes and tmexCD2-toprJ2 in Sequence Type 11 Carbapenem Resistant Klebsiella pneumoniae Strains - Li, Xi; Wang, Weizhong; Jin, Xi; Zhang, Xiaofan; Zou, Xuehan; Ma, Qiang; Hu, Qingfeng; Huang, Haijun; Tu, Yuexing (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives To characterize two plasmids co-harboring carbapenem resistance genes and tmexCD2-toprJ2 in carbapenem-resistant Klebsiella pneumoniae (CRKP) strains. Methods Two clinical CRKP strains were isolated and characterized by antimicrobial susceptibility testing, conjugation assays, whole-genome sequencing, and bioinformatics analysis. Results The two CRKP strains NB4 and NB5 were both resistant to imipenem, meropenem and tigecycline. Whole-genome sequencing revealed that two CRKP strains belonged to the ST11 type and carried multiple resistance genes. The tmexCD2-toprJ2 clusters in both strains were located on the IncFIB(Mar)-like/HI1B-like group of hybrid plasmids, which co-harbored the metallo-β-lactamase gene blaNDM-1. In addition, the co-existence of blaNDM-1 and blaKPC-2 and the presence of tmexCD2-toprJ2 in CRKP strain NB5 was observed. Conclusions In this study, tmexCD2-toprJ2 gene clusters were identified in two NDM-1-producing CRKP ST11 strains. These gene clusters will likely spread into clinical high-risk CRKP clones and exacerbate the antimicrobial resistance crisis. In addition, we detected the co-occurrence of blaNDM-1, blaKPC-2 and tmexCD2-toprJ2 in a single strain, which will undoubtedly accelerate the formation of a “superdrug resistant” bacteria. Hence, effective control measures should be implemented to prevent the further dissemination of such organisms in clinical settings.